Pengembangan Sistem Informasi Berbasis Web Penjurian Online untuk Pengelolaan Data Kegiatan Pupuk Kaltim Inovation Award pada Departement Inovasi dan Pengembangan Manajemen PT. Pupuk Kalimantan Timur - Farah Shofiatul Ummah; Fajar Pradana; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
PT. Pupuk Kalimantan Timur annually holds Pupuk Kaltim Inovation Award (PIA) which is a forum for employee to participate in order to create inovation in all lines of corporate activitis for quality improvement. Based on intervews with PIA managers can be concluded that until now all PIA activities are done manually, such as checking the originality of the paper by tim telaah that can be less efficient implementation due to the number of papers, has no priority selection rule for determining permanent judges so the judges can change uncexpectedly that can be less consistency in the assessment activities, and the assessment process that judges have to adjust the form when doing the assesment with the type of clster that is assessed because each type has different assessment form. To cover the issues is to develop a website with internal plagiarism check feature, judges recomendations feature, and online assessment feature. This research begins by analyzing system requirements, design then implementation. In this research using cosine similarity algorithm for the application of internal plagiarism check feature, and weighted product algorithm for application of judges recommendation feature. The testing is done by using unit testing, validation testing, and usability testing. The result of the validation test shows that the system can work well in accordance with the needs, and for the results of usability tests show the result of the score of 95.2% so can be concluded that the role of the system in accelerating and facilitate the activity of this juries have been met.